Transient TKI-resistant CD44+pBAD+ blasts undergo intrinsic homeostatic adaptation to promote the survival of acute myeloid leukemia in vitro - Xu, Yi; Baylink, David J.; Chen, Chien-Shing; Tan, Laren; Xiao, Jeffrey; Park, Brandon; Valladares, Ismael; Reeves, Mark E.; Cao, Huynh (Frontiers in Oncology, 2023)
Acute myeloid leukemia (AML) patients have frequent mutations in FMS-like receptor tyrosine kinase 3 (FLT3-mut AML), who respond poorly to salvage chemotherapies and targeted therapies such as tyrosine kinase inhibitors (TKIs). Disease relapse is a common reason of treatment failures in FLT3-mut AML patients, but its intracellular refractory mechanism remains to be discovered.In this study, we designed serial in vitro time-course studies to investigate the biomarkers of TKIresistant blasts and their survival mechanism. First, we found that a group of transient TKIresistant blasts were CD44+Phosphorylated-BAD (pBAD)+ and that they could initiate the regrowth of blast clusters in vitro. Notably, TKI-treatments upregulated the compensation pathways to promote PIM2/3-mediated phosphorylation of BAD to initiate the blast survival. Next, we discovered a novel process of intracellular adaptive responses in these transient TKI-resistant blasts, including upregulated JAK/STAT signaling pathways for PIM2/3 expressions and activated SOCS1/SOCS3/PIAS2 inhibitory pathways to down-regulate redundant signal transduction and kinase phosphorylation to regain intracellular homeostasis. Finally, we found that the combination of TKIs with TYK2/STAT4 pathways-driven inhibitors could effectively treat FLT3-mut AML in vitro.In summary, our findings reveal that TKI-treatment can activate a JAK/STAT-PIM2/3 axismediated signaling pathways to promote the survival of CD44+pBAD+blasts in vitro. Disrupting these TKIs-activated redundant pathways and blast homeostasis could be a novel therapeutic strategy to treat FLT3-mut AML and prevent disease relapse in vivo.